Bureaucratic competence and procurement outcomes - Francesco Decarolis; Leonardo Giuffrida; Elisabetta Iossa; Vincenzo Mollisi; Giancarlo Spagnolo (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
To what extent does a more competent public bureaucracy contribute to better economic outcomes? We address this question in the context of the US federal procurement of services and works, by combining contract-level data on procurement performance and bureau-level data on competence and workforce characteristics. We use the death occurrences of specific types of employees as instruments and find that an increase in bureau competence causes a significant and economically important reduction in: i) time delays, ii) cost overruns, and iii) number of renegotiations. Cooperation within the office appears to be a key driver of the findings.
Keywords: D44; H11; H57; 330; buyer quality; competence; procurement; public management; state capacity